Axial to Centrifugal Continuous Flow LVAD Pump Exchange Using Minimally Invasive Technique. Issue 6 (November 2017) - Pawale, Amit A.; Farkash, Ariel; Pandis, Dimosthenis; Anyanwu, Anelechi C.
Driveline or device infection may complicate left ventricular assist device implants, and only curative option may be pump exchange. Replacement with similar device may be liable to reinfection, because pump configuration is such that the new device and driveline may partly lie within the pocket of the previous pump. One approach to overcome this is using a different pump design such that the new pump would lie in a different location from the old pump. We describe treatment of severe HeartMate II (Abbott, [St Jude Thoratec Corp], Pleasanton, CA USA) left ventricular assist device infection by minimally invasive exchange to an intrapericardial HVAD (HeartWare International, Inc, Framingham, MA USA) left ventricular assist device.